Pleomorphic adenoma of the nasal cavity in a 21 - year - old patient - case report - Malwina Pomianek; Seweryn Ziajor; Artur Bednarski; Tomasz Piasecki; Katarzyna Makara; Victor Celarek; Paweł Rogalski; Karolina Makara (Kazimierz Wielki University, 2024)
Introduction and aim: Adenoma pleomorphum (multiform adenoma) is the most popular bening tumor, that originates from the salivary glands. Neoplasm develops mainly from large salivary glands and its occurrence in the nasal cavity is rare and falls mainly in the 3-6 decade of life. Only 1% of all pleomorphic adenomas develop in the nasal and sinus cavities. Despite being a benign tumor, malignant transformation can occur in 2-10% of cases. Description of the case: We report a case of a 21-year-old female ethnically Polish patient with nasal multiform adenoma with initial diagnosis, which indicated a polyp. The final diagnosis was based on the histopathological examination of the resected lesion. The tumor was removed by an endoscopic method with no tissue margins, which may increase the risk of recurrence. Conclusions: Our case demonstrates that despite pleomorphic adenomas typically occurs in the 3rd to 6th decade of life,  clinical symptoms are nondistinctive with a polyp and nasal cavity is a very rare location there should be always be increased vigilance leading to choosing best diagnostic measures to form right diagnosis.